Method and apparatus for switching data in communication system - Lee; Chen-Yi; Liu; Chih-Hao; Lin; Chien-Ching; Chang; Hsie-Chia; Hsu; Yar-Sun (My University, 2010)
A method and apparatus for switching data in communication system which comprises of mainly a conversion circuit to receive source data possessing real coding dimension and covert it to converted data possessing tolerable coding dimension; judgment bit is set in the converted data to designate the data as source data or not. Later on, shift circuit is used to shift the converted data in certain amount so as to generate a shifted data; meanwhile, the lowest bit and highest bit of shifted data are used to start acquiring real coding dimension to be used respectively as a first data and a second data, or by changing the pattern of acquiring the first data, then the highest bit minus the real coding dimension bit as the starting bit of the first data, and acquiring the real coding dimension from the side of the lowest bit. Finally, a comparison and selection circuit is used to compare the corresponding judgment bit in the first and the second data and to output an output data, wherein output data is source data with the above-mentioned amount of shift.